2022
DOI: 10.3390/antibiotics11040506
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Antimicrobial Prophylaxis in Pediatric Patients Undergoing Plastic Surgery: A RAND/UCLA Appropriateness Method Consensus Study

Abstract: For many years, it was clearly shown that surgical procedures might be associated with surgical site infection (SSI). Many scientific institutions prepared guidelines to use in surgery to reduce abuse and misuse of antibiotics. However, in the general guidelines for surgical antibiotic prophylaxis, plastic surgical procedures are not addressed or are only marginally discussed, and children were almost systematically excluded. The main aim of this Consensus document is to provide clinicians with recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Current antibiotic prophylaxis strategies may also require re-evaluation, possibly integrating alternative or adjunctive preventative measures. 36 Gosain et al found that the rate of major complications, defined as unplanned reoperation for expander removal, expander rupture, and exposure, was 41.5%. 33 Our study revealed a 39% rate of major complications, most commonly premature explantation due to infection and extrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current antibiotic prophylaxis strategies may also require re-evaluation, possibly integrating alternative or adjunctive preventative measures. 36 Gosain et al found that the rate of major complications, defined as unplanned reoperation for expander removal, expander rupture, and exposure, was 41.5%. 33 Our study revealed a 39% rate of major complications, most commonly premature explantation due to infection and extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicates a potential need for further research into optimizing antibiotic regimens, potentially involving longer durations or tailored approaches based on wound cultures. Current antibiotic prophylaxis strategies may also require re-evaluation, possibly integrating alternative or adjunctive preventative measures 36 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, perioperative antibiotic prophylaxis should be administered when surgery is needed [ 42 ]. A multidisciplinary approach is highly recommended, including an infectious disease specialist and a plastic surgeon.…”
Section: Burns With Overlapped Staphylococcal Infectionsmentioning
confidence: 99%
“…This document describes the current knowledge on risk factors for SSIs in neonates and children undergoing surgery and has the purpose of providing guidance to health care professionals for the prevention of SSIs in this population. Our aim is to consider the possible non-pharmacological measures that can be adopted to prevent SSIs, except the use of antibiotics, for which we refer to the specific papers of the Peri-Operative Prophylaxis in Neonatal and Paediatric Age (POP-NeoPed) Study Group [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. To our knowledge, this is the first study to provide recommendations based on a careful review of the available scientific evidence for the non-pharmacological prevention of SSIs in neonates and children.…”
Section: Introductionmentioning
confidence: 99%